Proses Pembuatan Gerabah Seni Dengan Teknik Pilin Sebagai Upaya Untuk Meningkatkan Hasil Produksi Keramik Bakaran Rendah Di Desa Kedungsari Kecamatan Tarokan Kabupaten Kediri - Herman Sugianto; Sepbianti Rangga Patriani; Tantra Sakre; Ika Ismurdiyahwati; Suparman; Hariadie (Universitas PGRI Adi Buana Surabaya, 2022)
Kedungsari village is one of the areas in the west of the city of Kediri, the majority of the population is working as farmers. Apart from being farmers, there are some people who work as pottery craftsmen where the resulting production tends to meet daily necessities such as boys, jugs and others. The touch of art on the work produced has not yet been applied to their products, so the work produced is more likely to be the same as other pottery craftsmen. The wealth of land as a basic material in the manufacture of grabah products in Kedungsari village is quite large and abundant to be considered and developed further as an effort to increase the income of the local community. Olek, therefore, it is necessary to hold socialization and training to produce good works of art pottery. The implementation of this assistance is carried out in 3 stages, including: planning, implementation and evaluation, the subject of this activity is 10 students majoring in Fine Arts Education and youth youth organizations in Kedungsari Village. From the results of this mentoring activity, it can be concluded that there was an increase in the skills and understanding of the participants who took part in the process of making art pottery. In addition, the results of this assistance provide improvements to the resulting product.